(untitled) - Thomas, Will (London, 2009)
Thomas, a performance coach and trainer who directs educational coaching organizations in the UK, and Smith, a trainer in modern learning methods who also works in motivation, explain how coaching methods can be used education. They detail what coaching is, how to coach, basic and advanced techniques, and benefits to schools, colleges, and universities, as well as aspects like communication improvement, the role of beliefs, using questions, differences from counseling and mentoring, coaching the reluctant, and self-development and management. This edition updates chapters and incorporates new evidence and case studies.
Keywords: Mentoring in education,Academic achievement,School improvement programs,School personnel management